Composição corporal e índices biométricos do pacu, Piaractus mesopotamicus Holmberg, 1887 (Osteichthyes, Characidae) submetido a ciclos alternados de restrição alimentar e realimentação - Souza, Valéria Leão; Urbinati, Elisabeth Criscuolo [UNESP]; Gonçalves, Daniela Chainho; Silva, Paulo César (My University, 2002)
The present paper evaluated, through hepatosomatic/mesenteric fat indexes and body composition, the pacu energy utilization when submitted to alternated food restriction/refeeding cycles during the growout period. Juveniles were distributed in three pounds and submitted to different feeding programs: A (ad libitum daily feeding), B (4-week feeding restriction and 9-week refeeding) and C (6-week feeding restrictions and 7-week refeeding), totaling 13 weeks for each cycle (4 experimental cycles). At the end of the periods, fish were sampled to obtain biometrics and biochemical data. The results showed that, during the first two cycles, C treatment obtained the best compensatory growth. Carcass lipid and water contents were inversely related, with body fat decrease. Fishes under B and C treatment during food restriction utilized liver and mesentery energy stores. These parameters were re-established in the refeeding phase, in all cycles.
Body composition and biometric indexes of the pacu, Piaractus mesopotamicus Holmberg, 1887 (Osteichthyes, Characidae) related to alternate cycles of feed and re-feeding constraints
Keywords: Body composition; Feeding management; Fish; Hepatosomatic index; Mesenteric fat index; fat; water; animal experiment; biometry; body composition; body fat; carcass; controlled study; diet restriction; energy; energy resource; feeding; feeding behavior; fish; growth; growth period; information processing; juvenile; liver; mesentery; nonhuman; refeeding; sample; time; water content; Animalia; Characidae; Osteichthyes; Piaractus; Piaractus mesopotamicus; Pisces; Vertebrata